Summaries of cases visited by the almoner - Cornish, F.
1901-12-30 1901 1900s 6 pages Spinks — Alfred — 10374 Visited 70 Avondale Rd Saw Mr. Spinks who said he was a painter and in the summer could earn £2 a week (when at work) and up to this year had gone to work in the gas factory in the winter but could not do so this winter as his chest was too weak. He had done no work to speak of for the last 4 months. His own and his wife's relations had assisted them but none of them had much to spare as they were nearly as poor as himself. The family consisted of himself, wife and two young children, his wife earns what she can now by needlework about 8/- or 10/- a week, Mr. Spinks belongs to no Club, said he did not believe in slate clubs, and had never thought of joining any other of the larger societies. They occupy half a house and stand at 5/6 a week rent, the rent book showed they were in arrears 16/-. Mr. Spinks gave as his principle employer Mr Marsh of 1 Black Boy Lane, who said he had known Spinks for about 18 years as a steady hardworking man. Mr. Marsh blamed him for not joining a club. Hospl Case Bronchitis Roots — Herbert 10271 Visited 12 Harringay Rd after calling 3 or 4 times I found a little girl at home so left a note to give to her father. In the answer Mr. Roots states he is a widower with 7 children, the eldest Alice works in the Fever Hosp St Anns Rd, has 2 sons Bert & Fred in the Army, Leonard 15 working with him, and the 3 youngest going to school, the eldest of these 3 May 12 looks after the two younger ones — 10 & 8 — Mr. Roots states his wages are 30/- a week and his son's 5 they have been working at Mr. Shaw's Liverpool Rd Holloway for the last six months, they live in a flat the rent of which is 8/6 a week. The people living on the next floor [informed] confirmed the above and informed agent that the eldest daughter never comes to the house, nor either of the sons which are soldiers, that Mr. Roots has to loose a good deal of time on account of his health, that he is a very steady man and they think it very hard of the eldest daughter that she will not assist her father and the younger children. Dr Morison Insuff. Infn 378/IMSW/A/1/6/8a